(untitled) (American Journal of Business Management, Economics and Banking, 2023)
This article discusses topical issues of conducting a pre-investigation check in a criminal case. In the world criminal proceedings, special attention is paid to ensuring the “right of an individual to a trial within a reasonable time”, improving the criteria and forms of differentiation of the criminal procedural form, critical assessment of existing procedural forms, the introduction of new procedural forms based on the public danger of a crime, the creation of effective mechanisms for resolving criminal disputes. In this regard, there is an urgent need to improve some institutions and the procedural order of investigative actions of the national criminal procedure legislation.